2011
DOI: 10.1007/s13369-011-0111-3
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Refactoring to Patterns on Software Quality Attributes

Abstract: The search for techniques to improve software quality and achieve robust, reliable, and maintainable software is ongoing. Refactoring, an approach that improves the internal structure of software without affecting its external behavior, is one method that aims to achieve better quality. Refactoring to patterns is another. The goal of this paper is to investigate whether refactoring to patterns improves software quality. This is done empirically by examining the metric values of external quality attributes for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…• Perform more analysis of the identified SPI success factors based on different variables like country, company's size, company's scope, job nature and different quality attributes [24,29]. • To explore the effectiveness of using snow balling technique with the automatic search.…”
Section: Discussionmentioning
confidence: 99%
“…• Perform more analysis of the identified SPI success factors based on different variables like country, company's size, company's scope, job nature and different quality attributes [24,29]. • To explore the effectiveness of using snow balling technique with the automatic search.…”
Section: Discussionmentioning
confidence: 99%
“…In earlier studies, we found that neither refactoring to patterns nor other refactoring methods necessarily improve software quality [5,6]. These results motivated us to investigate the effect of each refactoring method on particular software quality attributes rather than on quality in general.…”
mentioning
confidence: 90%
“…Alshayeb conducted experiments to validate the claims that software refactoring and refactoring to patterns improve software quality [5,6]. He found that refactoring and refactoring to patterns do not necessarily improve software quality.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The subject systems were selected from different domains (Java parser, class browser, neural networks and file manager) and different system sizes (number of classes range from 9-202). In this study, we focus on studying the effect of refactorings at the classlevel not at the overall system-level [34]. Therefore, the size of the system is not crucial.…”
Section: B Software Systems Backgroundmentioning
confidence: 99%